Validitas dan Praktikalitas E-Modul Struktur Atom Berbasis Pendekatan Saintifik Pada Kelas X SMA/MA - Juilando, Fatria (RC-INSTITUT, 2019)
The learning proces with the curriculum 2013 refers to the scientific approach. The purpose of this research is to develop e-module based on a scientific approach to class X SMA/MA and determine the level of validity and practicality of  e-modules depeloped. The type of this research is research  and development (R&D) with a 4-D development model. E-module which is caried out is validity and practicality test. The validity test was carried out by 2 chemistry lectures at FMIPA UNP, 3 chemistry teachers at SMAN 8 Padang, while the practicality test is carried out by 3 chemistry teachers of SMAN 8 Padang and 30 students of class X IPA 5 SMAN 8 Padang in 2019/2020. The instrument used for this research was a validity questionnire and practicality questionnaire whose results will be analyzed using the cohen kappa formula. This research  produced an atomic structure, e-module based on scientific approach with a mean moment of kappa is 0,85 with a very high level of validity. The results of the teacher practicality test and the practicality test of the students obtained an average of kappa moments sequentially  were 0,85 and 0,84 with very high degree of  practicality.